2016
DOI: 10.1111/nyas.13053
|View full text |Cite
|
Sign up to set email alerts
|

Novel brain‐penetrating oximes for reactivation of cholinesterase inhibited by sarin and VX surrogates

Abstract: Current oxime reactivators for organophosphate-inhibited cholinesterase (ChE) do not effectively cross the blood–brain barrier and therefore cannot restore brain ChE activity in vivo. Our laboratories have studied highly relevant sarin and VX surrogates, which differ from their respective nerve agents only in the leaving group and thereby leave ChE phosphylated with the same chemical moiety as sarin and VX. Our laboratories have invented novel substituted phenoxyalkyl pyridinium oximes (U.S. Patent 9,227,937 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…[90] In order to facilitate reactivation in the central nervous system (CNS), Chambers et al took the unique approacho f continuing to use pyridinium-based oximes but lengthened the phenoxylalkyl chains such that the lipophilicity increases, thereby providing for anticipated penetration into the CNS. [94,95] Although previously outlined by Kuca et al,r ecent work using lethal doses of nerve agent analogues have been conducted in which two compounds show an increasei ns urvival rates and earlier cessation of symptoms compared to those of 2-PAM. [93,95] The Chambers study made use of two nerve agent surrogates-one for sarin and one for VX-and evaluated four novel lipophilic oximes, alongw ith 2-PAM, to test survival rates after LD 99 challenges.…”
Section: Recent Results From Efforts To Develop Broad Scope Reactivatmentioning
confidence: 99%
See 2 more Smart Citations
“…[90] In order to facilitate reactivation in the central nervous system (CNS), Chambers et al took the unique approacho f continuing to use pyridinium-based oximes but lengthened the phenoxylalkyl chains such that the lipophilicity increases, thereby providing for anticipated penetration into the CNS. [94,95] Although previously outlined by Kuca et al,r ecent work using lethal doses of nerve agent analogues have been conducted in which two compounds show an increasei ns urvival rates and earlier cessation of symptoms compared to those of 2-PAM. [93,95] The Chambers study made use of two nerve agent surrogates-one for sarin and one for VX-and evaluated four novel lipophilic oximes, alongw ith 2-PAM, to test survival rates after LD 99 challenges.…”
Section: Recent Results From Efforts To Develop Broad Scope Reactivatmentioning
confidence: 99%
“…[94,95] Although previously outlined by Kuca et al,r ecent work using lethal doses of nerve agent analogues have been conducted in which two compounds show an increasei ns urvival rates and earlier cessation of symptoms compared to those of 2-PAM. [93,95] The Chambers study made use of two nerve agent surrogates-one for sarin and one for VX-and evaluated four novel lipophilic oximes, alongw ith 2-PAM, to test survival rates after LD 99 challenges. It was found that the use of 1 and 2 ( Figure 10) increased the survival rate to 65 and 55 %, respectively,a nd when combined with 2-PAM, the survival rates increased to 73 and 80 %, respectively,r elative to the 40 %2 -PAM control for as arin analogue.…”
Section: Recent Results From Efforts To Develop Broad Scope Reactivatmentioning
confidence: 99%
See 1 more Smart Citation
“…7. 18,46 These phenoxyalkyl pyridinium oximes have alkyl chains of 3-5 carbons, with various substitutions on the phenoxy group. Although it contains a quaternary ammonium, similar to other pyridinium oximes that do not cross the BBB, it is hypothesised that the phenoxyalkyl moiety could increase the lipophilicity of the oxime thus providing counterbalance to the positive charge from the quaternary ammonium, hence allowing BBB penetration.…”
Section: Development Of New Structural Oximesmentioning
confidence: 99%
“…7,9 In addition to this potential lethality of this overstimulation, of great concern also is the fact that AChE inhibition by OPs in the CNS can lead to seizures occurring from an excess of ACh-mediated activation of the excitotoxic glutamatergic pathways which can prolong seizures and thus lead to brain damage. 17,18 It has also been suggested that exposure to sub-lethal doses of OP can dramatically impact CNS mediated behavioural attributes such as decreased ability to perform tasks. 12 All the currently available oxime reactivators are quaternary oximes.…”
Section: Introductionmentioning
confidence: 99%